Co-occurring self-efficacy, anxiety, and depression in caregivers of patients with heart failure: A Group-Based Dual-Trajectory Modeling Approach - Qingyun Lv; Hairong Chang; Yaqi Wang; Xueying Xu; Jingwen Liu; Yuan He; Li Fu; Mei Lin; Xinxing Gao; Xiaoying Zang; Xiaonan Zhang (BMC Nursing)
Abstract Background Self-efficacy and mental health present mutually influencing relationships in caregivers of patients with heart failure (HF). There is currently a lack of understanding the synergistic developmental mechanisms of self-efficacy, anxiety, and depression in caregivers. The purpose of the study was to examine the individual and dual trajectories of caregiver self-efficacy, anxiety, and depression during the first three months after the discharge of patients with HF. Methods A prospective cohort study was conducted from June 2022 to May 2024, in four tertiary hospitals in Tianjin, China. A total of 299 family caregivers of patients with HF were enrolled in the cohort, and 267 completed follow-ups. Group-based dual trajectory modeling was employed to examine the development of self-efficacy, anxiety, and depression. Results The mean (SD) age of caregivers was 58.3 (13.1) years, and 164 (61.4%) were women. Three trajectories of caregiver self-efficacy were identified: low-curve (25.1%), middle-curve (67.8%), and high-stable (7.1%). Regular exercise, work status, and chronic disease were associated with the different caregiver self-efficacy trajectories. A 3-class trajectory solution was chosen for depression and anxiety when analyzed separately. The proportions of ideal combinations of high-stable self-efficacy and initial-to-mild anxiety or depression were extremely small, at 12.60% and 8.00%, respectively. Caregivers had limited and inconsistent abilities to regulate the effects of anxiety and depression on their self-efficacy. Conclusion The present study identified three distinct trajectories of self-efficacy, anxiety, and depression among family caregivers of patients with HF. The dual-trajectory models revealed the probability of interrelationships between caregiver self-efficacy trajectories and those of anxiety and depression, suggesting substantial opportunities to enhance caregivers’ self-efficacy and mental well-being of patients with HF.